2020
DOI: 10.1371/journal.pone.0228672
|View full text |Cite
|
Sign up to set email alerts
|

Bold or reckless? The impact of workplace risk-taking on attributions and expected outcomes

Abstract: Risk-takers are rhetorically extolled in America, but does this veneration ignore the downsides of failure? We test competing perspectives on how workplace risk-takers are perceived by examining cultural attitudes about individuals who successfully take, unsuccessful take, and avoid risks at work. The results of two experiments show that, in comparison to risk-avoidance, expected workplace outcomes are enhanced by successful risktaking and that failure does not appear to significantly harm expected workplace o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…By taking risks and failing, on the other hand, the individual learns something valuable about that decision and scenario and gains confidence in the future. According to previous research, successful risk-taking enhances outcomes in the workplace (e.g., being promoted), whereas failed risk-taking does not necessarily result in a disadvantage in the workplace [46].…”
Section: Discussionmentioning
confidence: 92%
“…By taking risks and failing, on the other hand, the individual learns something valuable about that decision and scenario and gains confidence in the future. According to previous research, successful risk-taking enhances outcomes in the workplace (e.g., being promoted), whereas failed risk-taking does not necessarily result in a disadvantage in the workplace [46].…”
Section: Discussionmentioning
confidence: 92%
“…It seems plausible to believe greater social acceptance may lead to increased job satisfaction. Risk-taking has also been linked to a greater sense of agency 49 , 50 . A higher sense of agency increases the possibility to influence one's own work, which in turn may lead to a higher sense of involvement, an important factor of job satisfaction 3 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of academicians' suitability for their roles to risk-taking behaviors shows that they may be open to risk. Fisk and Overton (2020) emphasized that risk reduces the perception of indecision and that risk-taking acts as a cultural mechanism that protects employees from punishment even if it fails. This shows that taking risks for the job can lead to positive results in terms of suitability for a role in academia.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Lu et al (2018) revealed in their research that interpersonal insecurity increases the tendency to take risks. Fisk and Overton (2020) in their research on successful or unsuccessful risktaking behaviors of employees in the workplace; stated that successful risk-taking will improve workplace results, while unsuccessful risk-taking will not create a disadvantage at work. They emphasized that although workplaces that take unsuccessful risks are perceived to be more likely to downsize, people who take unsuccessful risks are more likely to be hired and promoted (compared to risk-averse ones).…”
Section: Risk-takingmentioning
confidence: 99%